2017
DOI: 10.1007/s11769-017-0894-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RapidEye imagery’s red-edge band and vegetation indices on land cover classification in an arid region

Abstract: Land cover classification (LCC) in arid regions is of great significance to the assessment, prediction, and management of land desertification. Some studies have shown that the red-edge band of RapidEye images was effective for vegetation identification and could improve LCC accuracy. However, there has been no investigation of the effects of RapidEye images' red-edge band and vegetation indices on LCC in arid regions where there are spectrally similar land covers mixed with very high or low vegetation coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Because VI and PCs were linearly computed from spectral bands, their addition imported relevant, even redundant information, which might have led to accuracy losses. Although many studies indicated that the addition of VI contributed to the classification [19,41], some others also supported the conclusion in this study. For example, Adelabu et al [22] reported that, when using all the bands of RapidEye imagery, adding NDVI decreased the classification accuracy.…”
Section: Feature Selection Results For Sbs Following the Addition Of supporting
confidence: 75%
“…Because VI and PCs were linearly computed from spectral bands, their addition imported relevant, even redundant information, which might have led to accuracy losses. Although many studies indicated that the addition of VI contributed to the classification [19,41], some others also supported the conclusion in this study. For example, Adelabu et al [22] reported that, when using all the bands of RapidEye imagery, adding NDVI decreased the classification accuracy.…”
Section: Feature Selection Results For Sbs Following the Addition Of supporting
confidence: 75%
“…The test was based on the error matrix of two classifications and the chi-squared statistic value (χ 2 ) with one degree of freedom was calculated as follows: where f ij is the number of samples that are correctly classified by classification scheme i and incorrectly classified by classification scheme j (i = 1, 2; j = 1, 2). The difference between two classification schemes is statistically significant at the 95% confidence level ( p = 0.05) when the χ 2 value is greater than or equal to 3.84 [ 65 , 66 ]. In this study, McNemar’s test was used to evaluate whether there were significant differences in the classification accuracy between two classification schemes by RF classifier with different red edge features.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [47] performed a paired t-test [88]. McNemar tests were used in some other studies, such as those described in Duro et al [89], Li et al [12], Li et al [90,91], and Maxwell et al [31]. In addition, a Mann-Whitney U-test [92] was used by Fassnacht et al [93].…”
Section: Selection Of Statistical Test Methods and Effects Of Test Setmentioning
confidence: 99%
“…It is worth noting that the McNemar test [87] is designed for two-class classification, while the other two tests are intended for multi-class classification. Because the McNemar test [87] is easy to implement compared to the t-and U-tests [88,92], it is also widely used for multi-class classification with relative reasonable results, such as in the above-mentioned studies [12,31,57,84,[89][90][91]. However, when the test set is large, this method is not applicable.…”
Section: Selection Of Statistical Test Methods and Effects Of Test Setmentioning
confidence: 99%